Determination of Human Resource Management Strategies Enhancing Academic Staff Job Commitment in Colleges of Education in Delta State - Ezugoh, Theodorah Chinelo; Mbonu, Obianuju Adaobi (International Journal of Educational Management, 2021)
This study determined human resources management strategies enhancing academic staff job commitment in colleges of education (COEs) in Delta State. Three research questions guided the study. The study employed a descriptive survey research design. The study population constituted all the 1,051academic staff from the four colleges of education (COE) in Delta State. The sample size for the study comprised a total of 526 academic staff from the COEs, selected at 50% from the entire population using the stratified random sampling technique. A research instrument titled: "Determination of Human Resource Management Strategies Enhancing Academic Staff Job Commitment Questionnaire (DHRMSEASJCQ)" was used for data collection. The research instrument's reliability was established through a pilot-test. Data collated were analysed using mean statistics rated at 2.50 and the standard deviation. The study's findings established that human resources management strategies enhanced academic staff job commitment. From the findings of the study, recommendations were made.